2016
DOI: 10.1177/2329488416672431
|View full text |Cite
|
Sign up to set email alerts
|

In the Ear of the Beholder: Self-Other Agreement in Leadership Communication and Its Relationship With Subordinates’ Job Satisfaction

Abstract: This article deals with the question of how agreement or disagreement in the perception of leadership communication from the perspective of both leader and subordinate is related to subordinates’ job satisfaction. Employees of a department in a large, globally operating insurance company and their managers ( N = 110) completed questionnaires including instruments to assess leadership communication from the perspective of the managers and their respective employees as well as employees’ job satisfaction. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
0
17
0
2
Order By: Relevance
“…Additionally, teachers' commitment was found to be impacted by school principals' leadership (Ross & Gray, 2006). According to Erben et al (2019), successful leaders can provide a high level of job satisfaction to subordinates and improve their working conditions. This has been reported in industries such as finance, healthcare and education, where studies on the association between leadership styles and work satisfaction were conducted (Abd Rahman et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, teachers' commitment was found to be impacted by school principals' leadership (Ross & Gray, 2006). According to Erben et al (2019), successful leaders can provide a high level of job satisfaction to subordinates and improve their working conditions. This has been reported in industries such as finance, healthcare and education, where studies on the association between leadership styles and work satisfaction were conducted (Abd Rahman et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that overestimations by leaders of their own positive characteristics are associated with poorer employee outcomes, such as lower job satisfaction (Amundsen & Martinsen, 2014;Erben et al, 2019), and higher turnover intention (Amundsen & Martinsen, 2014). Simply, mechanisms underlying over-estimations are a lack of self-awareness, arrogance (Atwater et al, 1998), and narcissism (Judge et al, 2006) and such overestimations may hurt the relationship (Moshavi et al, 2003).…”
Section: Consequences Of (In)congruent Perceptionsmentioning
confidence: 99%
“…Some later studies have confirmed the relationship between SOA and job satisfaction and added that overestimation (i.e. leaders rating their leadership higher than subordinates do) was related to poorer job satisfaction among subordinates (Amundsen and Martinsen, 2014;Erben et al, 2016;Moshavi et al, 2003). In addition, agreement has been related to lower turnover intention among subordinates (Sim, 2018), whereas leaders' overestimation was related to higher turnover intention (Amundsen and Martinsen, 2014).…”
Section: Leader Consequences Of Self-other Agreementmentioning
confidence: 92%